Math-a-POLKA: Mathematics as a Place of Loving Kindness and . . . - Khan, Steven; Armstrong, Alayne (Journal of the Canadian Association for Curriculum Studies, 2019)
In proposing this special issue, we sought to open a generative and healing conversation in the intersectionality of love, kindness, mathematics, curriculum and education, offering a call that invited the completion of the sentence, "I imagine/want mathematics to be a place of loving kindness and . . . " In their responses, contributors have highlighted the importance of communication in establishing loving kindness through patterns of caring responsiveness, acts of imagination and empathy, and conversations that matter. They envision a place of learning that values aesthetic and affective engagement in mathematical and pedagogical practices that promote capability and resilience among students. As guest editors, we each offer our responses to the prompt, exploring “kind-ness” as belonging and challenging readers to expand that further to the “kin’d-ness” of communal relations of multi-species flourishing, thus reimagining mathematics.